1997
DOI: 10.1029/97jd00012
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of sulfuric acid/water aerosols: Freezing characteristics

Abstract: Abstract. A low-temperature flow cell has been used in conjunction with a Fourier transform infrared (FT-IR) spectrometer to study sulfuric acid/water aerosols. The aerosols were generated with a wide range of composition (28 to 85 wt %), including those characteristic of stratospheric sulfate aerosols, and studied over the temperature range from 240 K to 160 K. The particles exhibited deep supercooling, by as much as 100 K below the freezing point in some cases. Freezing of water ice was observed in the more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 32 publications
5
57
1
Order By: Relevance
“…This is in agreement with bulk and aerosol studies that had difficulty freezing aerosols of composition greater than 35 wt % H 2 SO 4 . 4,10,12,14 In general, it is seen that our data are in good agreement with the historic work. We will now discuss specific transitions that are relevant to atmospheric aerosols.…”
Section: Resultssupporting
confidence: 94%
“…This is in agreement with bulk and aerosol studies that had difficulty freezing aerosols of composition greater than 35 wt % H 2 SO 4 . 4,10,12,14 In general, it is seen that our data are in good agreement with the historic work. We will now discuss specific transitions that are relevant to atmospheric aerosols.…”
Section: Resultssupporting
confidence: 94%
“…There is super‐cooling of up to 25 K compared to SAT without any indication that the hydrate formed despite the long observation time. Thus, earlier studies [ Martin et al , 1997; Carleton et al , 1997; Anthony et al , 1995; Clapp et al , 1997], where freezing was not detected above the ice frost point, are confirmed by these temperature cycles. During the period when ice covered the walls below 210 K, the observed particle compositions follow the metastable coexistence line of the liquid solutions with ice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the observation of these stratosphere‐like particles over days can be used to evaluate the probability of phase changes under stratospheric conditions. In the past, particle freezing has been investigated either for larger droplets [ Martin et al , 1997; Carleton et al , 1997] or for particles in stratospheric size ranges over shorter time scales of at most a few hours [ Anthony et al , 1995; Clapp et al , 1997]. Freezing of sulfate aerosols above the ice frost point has not been observed in these previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…A growing crystal interface incorporates solute molecules to a degree dependent on the thermodynamics of phase transformation, which are highly dependent on solution composition [ Wolten and Wilcox , 1967]. The physical chemistry of freezing nucleation in concentrated aqueous solutions is an active area of current research [ Clapp et al , 1997; Tabazadeh and Toon , 1998; Bertram et al , 2000]. In dilute solutions, such as cloud and rain drops with radii greater than 1 μm, ice is known to be very exclusionary of most solutes (i.e., solute solubility in ice is very small) (see Hobbs [1974, pp.…”
Section: Development Of a Theory‐based Indicator Of Retentionmentioning
confidence: 99%